Baja California universitaria gen. N., sp. N. (capsalidae: monogenea) parasite of three species of paralabrax (serranidae: actynopterigii) from the baja California peninsula, Mexico. - del Prado-Rosas, Gómez (2023)
Serranid fishes are distributed around the world in tropical and warm temperate waters and are some of the most commercially important reef species. The 10 species of serranid fish of the genus Paralabrax Girard, 1856, are confined to the coasts of America, being located mainly in the Pacific Ocean, including the Gulf of California, with five of them occurring on both coasts of the Baja California peninsula, Mexico. A total of 278 fish of three species of Cabrillas of the Paralabrax genus [P. auroguttatus Walford, 193; P. clathratus (Girard, 1856) and P. nebulifer (Girard, 1856)] were obtained from various locations in the Gulf of California and the Pacific Ocean and were parasitized on lower pharyngeal plate and gills with a monogenean species of the Capsalidae family. The characteristic of the aseptate opisthohaptor is shared with the genera of four subfamilies: Entobdellinae, Nitzschiinae, Benedeniinae and Encotyllabinae. They differ from the five genera of the subfamily Entobdellinae by not having a prohaptor formed by two elongated, slightly depressed glandular areas. They differ from the only genus of Nitzschiinae by not having prohaptor in the form of botryans. They differ from the 17 genera of the Benedeniinae subfamily because their representatives have the opisthohaptor with a widened circular shape and because they have a vagina. Finally, although due to the general morphology of the body, more cylindrical than ovoid, the specimens in this work show more similarity with the specimens of the two recognized genera of the Encotyllabinae subfamily, they differ from them by not having an opisthohaptor with a very long peduncle and two pairs of hooks, one of which is very large, occupying a large part of its area, as well as not having a vagina. Due to the characteristics of the opisthohaptor (semipedunculated, without septa oval, with a narrow opening and bordered by a marginal membrane), a new genus and species are proposed as Bajacalifornia universitaria. Until we have a molecular study to confirm it, in this work they are included in the Encotyllabinae subfamily.